Corrections Education at the Nexus of Science and Practice: A History of Conscience and Convenience in Achieving Professionalization. Issue 4 (1st October 2016) - Lutze, Faith E.
Abstract : Education has long been viewed as a means to professionalize corrections work. Contemporary emphasis on using science to inform evidence-based corrections highlights the need for a professional, highly educated, and experienced workforce. Over time, colleges and universities have served at the nexus of science and practice with higher education helping span the boundaries between research and the implementation of evidence-based practice in corrections. The professionalization of corrections through higher education, however, has not been without serious challenges. Throughout history, the ideals of reformers to professionalize corrections through higher education have been molded to fit the social, economic, and political needs of both universities and corrections organizations, thus diminishing the full potential of education and practice to meet the contemporary demands of evidence-based corrections.